2012
DOI: 10.1530/joe-12-0126
|View full text |Cite
|
Sign up to set email alerts
|

Effects of androgens on cardiovascular remodeling

Abstract: Androgens, the male sex hormones, exert various biological effects on many target organs through the transcriptional effects of the nuclear androgen receptor (AR). ARs are expressed not only in classical target organs, such as the brain, genital organs, bone, and skeletal muscles, but also in the cardiovascular system. Because the female sex hormones estrogens are wellknown to protect against cardiovascular disease, sex has been considered to have a significant clinical impact on cardiovascular mortality. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 103 publications
1
16
0
Order By: Relevance
“…75 Despite the many detrimental effects of testosterone, some studies revealed that androgens exert atheroprotective effects against cardiovascular disease at least in the elderly people, mediated by the androgen receptors. 85 Besides, lower levels of testosterone had harmful effect on AAA and on the cardiovascular system in men. 23 In conclusion, there are still many controversies and unanswered questions about the sex differences in AAA.…”
Section: Discussionmentioning
confidence: 99%
“…75 Despite the many detrimental effects of testosterone, some studies revealed that androgens exert atheroprotective effects against cardiovascular disease at least in the elderly people, mediated by the androgen receptors. 85 Besides, lower levels of testosterone had harmful effect on AAA and on the cardiovascular system in men. 23 In conclusion, there are still many controversies and unanswered questions about the sex differences in AAA.…”
Section: Discussionmentioning
confidence: 99%
“…Our observation that DHT induces both VEGF and NO suggests that the pro-angiogenic effects of DHT may be mediated via a cross-talk between them. Moreover, this may create a synergistic environment as VEGF has been shown to induce angiogenesis via NO generation and NO induces VEGF thereby creating a positive feedback angiogenic loop (Papapetropoulos et al 1997, Losordo & Isner 2001, Ikeda et al 2012.…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
“…Functional effects are elicited once AR is activated either directly or indirectly by interaction with specific coactivator proteins that regulate transcriptional responses [40]. In addition, current evidence indicates that testosterone activity is regulated through both AR-dependent and -independent mechanisms [9, 41]. NFAT/calcineurin signaling has been well established as a regulator of hypertrophic growth, and we here provide new insights regarding the mechanisms implicated in cardiac myocyte hypertrophy induced by testosterone.…”
Section: Discussionmentioning
confidence: 91%